Development of selective attention in preschool-age children from lower socioeconomic status backgrounds. (August 2017) - Hampton Wray, Amanda; Stevens, Courtney; Pakulak, Eric; Isbell, Elif; Bell, Theodore; Neville, Helen
Highlights: We assessed selective attention in 4-year-olds from lower & higher SES backgrounds. Development of selective attention over one year was evaluated in the LSES group. At age four, only the HSES group showed enhanced neural responses with attention. The LSES group developed an effect of attention on neural processing by age five. The LSES group showed persistent attenuation of distractor suppression at age five. Abstract: Although differences in selective attention skills have been identified in children from lower compared to higher socioeconomic status (SES) backgrounds, little is known about these differences in early childhood, a time of rapid attention development. The current study evaluated the development of neural systems for selective attention in children from lower SES backgrounds. Event-related potentials (ERPs) were acquired from 33 children from lower SES and 14 children from higher SES backgrounds during a dichotic listening task. The lower SES group was followed longitudinally for one year. At age four, the higher SES group exhibited a significant attention effect (larger ERP response to attended compared to unattended condition), an effect not observed in the lower SES group. At age five, the lower SES group exhibited a significant attention effect comparable in overall magnitude to that observed in the 4-year-old higher SES group, but with poorer distractor suppression (larger response to the unattended condition). Together, these findings suggest both a maturational delay and divergent developmental pattern in neural mechanisms for selective attention in young children from lower compared to higher SES backgrounds. Furthermore, these findings highlight the importance of studying neurodevelopment within narrow age ranges and in children from diverse backgrounds.